Strain distribution on shortened dental arches complete denture using finite element analysis - Jasmine; Ariyani; Nasution, Ismet Danial (Indonesian Journal of Prosthodontic, 2024)
Prosthetic management for edentulism could be challenging with the Inadequate interocclusal space due to enlargement of the maxillary tuberosity, causes difficulties in artificial tooth placement. Hence, reducing numbers of artificial teeth is indicated which is in line with the shortened dental arches (SDA) concept. The SDA concept could provide good occlusal and mandibular stability, comfort in mastication and appearance. An increase in strain distribution value in the anterior region of the mandible was found in the SDA due to partial changes of the occlusal load distribution pattern. Strain distribution can be analyzed using Finite Element Analysis (FEA). This literature review aims to analyse the strain distribution on SDA complete denture using finite element analysis. The SDA concept was aimed at preserving the anterior and premolar regions. Masticatory ability is correlated with the number of teeth and is impaired if there are less than 20 teeth. Based on FEA, the increase in strain distribution value in the SDA concept is due to changes in occlusal load distribution pattern, masticatory muscle activity and tissue morphology that is susceptible to stress. Nevertheless, the strain value in SDA models were of lower intensity than the yield reported to cause deterioration effects. In maxillary complete denture, the highest strain value was found at the incisal and labial frenal notches. Strain distribution on shortened dental arches using finite element analysis shows a satisfactory masticatory ability and an increase in the value of stress distribution in the anterior region of the mandible.